Association between dietary inflammatory index and cognitive impairment among American elderly: a cross-sectional study - Zhang, Yu; Peng, Yuanyuan; Deng, Wei; Xiang, Qian; Zhang, Wang; Liu, Maohang (Frontiers in Aging Neuroscience, 2024)
Background It has been shown that inflammation may be associated with cognitive impairment (CI). Diet modulates inflammation. However, there is currently a scarcity of epidemiological studies exploring the connection between the inflammatory potential of diet and CI. The objective was to investigate the correlation between the dietary inflammatory index (DII) and cognitive impairment in older adults in the United States. Methods The present investigation utilized a cross-sectional dataset obtained from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014. Dietary intake data was used to calculate DII scores, which were then used to categorize participants into quartiles. Participants’ cognitive function was assessed using the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD), Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST). Individuals who scored in the lowest quartile on any of these tests were classified as exhibiting low cognitive performance. The association between DII and cognitive impairment was investigated by multivariate logistic regression, smooth curve fitting, and subgroup analysis. Results A total of 947 older adults were enrolled in the study. Following the adjustment of confounding variables, DII scores exhibited a significant and positive correlation with low cognitive performance, as measured by AFT (OR 1.15, 95% CI 1.02–1.28, p = 0.02) and the DSST (OR 1.38, 95% CI 1.13–1.68, p = 0.004). Compared with the lowest quartile of DII, the highest weighted odds ratio of cognitive impairment based on AFT was observed in the fourth quartile group (OR 1.89, 95% CI 1.05–3.38, p = 0.03). Similarly, a comparable pattern was evident in DSST (OR 4.30, 95% CI 1.85–9.98, p = 0.003). Additionally, the smooth curve fitting results showed a nonlinear relationship between DII and cognitive decline evaluated by DSST (p for nonlinearity = 0.016). No interaction effects between cognitive impairment and age or gender were observed in relation to all cognitive test scores. Conclusion This research reveals a positive link between diet with higher inflammatory potential and cognitive decline among elderly individuals in America. However, additional studies on dietary interventions are necessary to explore the cause-and-effect relationship.